1960
DOI: 10.1109/ire-i.1960.5006902
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Beam Frequency Standards

Abstract: 10 An unsymmetrical power spectrum can arise when the carrier is frequency modulated with two or more different frequencies (36).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1961
1961
2005
2005

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Another circuit, based on a series of oscillators whose output frequency was locked to another signal 24 , was discovered later, around 1940, but some of the requirements mentioned above were not fulfilled.…”
Section: Development and Use Of Synthesizersmentioning
confidence: 99%
“…Another circuit, based on a series of oscillators whose output frequency was locked to another signal 24 , was discovered later, around 1940, but some of the requirements mentioned above were not fulfilled.…”
Section: Development and Use Of Synthesizersmentioning
confidence: 99%
“…Improvements Wf're made at all stages, hy better control of the transmitters, by more careful operation of the atomic standards and by ensuring that the measurements at different laboratories were averaged over the same periods. Caesium beam standards having an accuracy of a few parts in 10 10 were made at the National Physical Laboratory, U.K. , the National Bureau of Standards (Mockler, Beehler & Snider, 1960) and at the Laboratoire Suisse de Recherches Hologeres (Kartaschoff) Bonanomi & de Prins, 1960). An analysis of results obtained during the period July 1961 to December 1962 (Morgan Crow & Blair, 1965) showed that the three precise laboratory standards agreed to ± 1 part in 10 10 and that the agreement between seven different standards including commercial models was ±2 parts in 10 10 • An indication of the accuracy now achieved by using VLF transmissions is indicated in Table 1 which gives the measured values of the frequency of the GBR transmitter at the NPL, the NBS and LSRH for a period of 3 months in 1965.…”
Section: The Intercomparison Of Atomic Clocksmentioning
confidence: 99%
“…The frequency reference of the NBS standard frequency broadcasts is the USFS which consists of two cesium beam units [Mockler et al, 1960] …”
Section: Role Of Frequency Standards In Nbs Broadcastsmentioning
confidence: 99%
“…Laboratory models of atomic (cesium-beam) frequency standards were developed and built at NBS and in 1960 two such units became the basis of the USFS [Mockler et al, 1960]; continued improve ments followed [Beehler et al, 1962] WWVB (60 kc/s) broadcasts disseminated the USFS with a transmitted accuracy of several parts in 1011 (fractional frequency units) through control by transfer (working) atomic frequency standards. Regularly published corrections relate such values to the USFS as shown in figure 1.…”
Section: Introductionmentioning
confidence: 99%